AB1010 Achievement of Nice Quality Standards for Patients with New Presentation of Inflammatory Arthritis: Results from The Uk National Clinical Audit for Rheumatoid and Early Inflammatory Arthritis. (15th July 2016) - Ledingham, J.; Snowden, N.; Galloway, J.; Rivett, A.; Firth, J.; Macphie, E.; Kandala, N.; Rowe, I.; Ide, Z.; Dennison, E.; ,
Abstract : Background: The national audit office reported variation in the quality of services for patients with Inflammatory Arthritis (IA) in the UK in 2009. The Health Quality Improvement Partnership funded a national audit to explore this further. Objectives: We set out to assesses whether trusts in England & Wales are achieving the 7 quality standards (QS) published by the National Institute for Health & Care Excellence (NICE). Methods: All individuals >16 years presenting to specialist rheumatology services in England & Wales with suspected new onset IA were recruited. Clinician & patient derived data were collected against all NICE QS over the 1st 3 months of specialist care. Results: 6, 354 patients were recruited nationally from 1 February 2014 to 31 January 2015. 94% of trusts/health submitted data. Patients were predominantly female (66%); white British (79%); and of working age (70%). At recruitment 46% had a diagnosis of Rheumatoid Arthritis (RA); 16% undifferentiated inflammatory arthritis (EIA). Only 17% of patients were referred by their general practitioner (GP) within 3 days of first presentation (QS1); median time interval 34 days. Over 25% waited >3 months. 12% of referrals had no indication that EIA was suspected. Specialist assessment occurred <3 weeks of referral for 38% (QS2). The median time interval was 4 weeks, >25% of patients waited >7 weeks. Higher staffing levels (>1 consultant/100, 000 population) & the presence of EIA clinics were associated with shorter waiting times (odds ratio (95%CI) 1.3 (1.1–1.4) & 1.6 (1.4–1.7) respectively). Disease modifying anti-rheumatic drug (DMARD) initiation within 6 weeks of referral (QS3) was achieved in 53% of RA patients; 36% were treated with combination DMARDs & 82% with steroids. Clinicians reported that 59% of patients received structured education (QS4). Treat to target plans were set for 91% of patients. These targets were achieved in only 27% (QS5). Almost all trusts reported access to urgent advice (QS6) & incorporated annual review services (QS7). Conclusions: This audit has enabled English & Welsh rheumatology services to measure their performance against NICE QS for the early management of IA & RA, benchmarked to regional & national comparators for the first time. The findings clearly demonstrate where improvement is needed. Delays in referral from primary care as well as delays in offering a first appointment in secondary care have been identified as key barriers to effective early arthritis care. Disclosure of Interest: None declared